A Comparative Study of Identification Techniques for Fractional Models - JALLOUL Abdelhamid; Khaled JELASSI; Jean-Claude TRIGEASSOU (International Journal of Electrical and Computer Engineering (IJECE), 2013)
A comparative study of methods for fractional system identification is presented in this paper. The fractional system is modeled by the help of a non integer integrator which is approximated by a J+1 dimensional modal system composed of an integrator and first order systems. This identification method is compared to other techniques available in the Matlab toolbox. The model parameters are estimated by an output-error technique using a non linear iterative optimization algorithm. Numerical simulations show the performance of the modal approach for modeling and identification.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2130